Determinants of the political process in the Middle East - A. M. Israilov (Современная наука и инновации, 2024)
The political process in the Middle East is distinguished by a large number of determining factors, which together form a complex system of functioning of the political system of regional societies. Each country in the Middle East has a set of general and specific features of the political process, which determines the unique characteristics of Middle Eastern political life. The presence of a significant array of ethno-confessional, historical, civilizational, socioeconomic features of the region predetermines research interest in the stated topic. At the same time, the political process in the Middle East is constantly changing under the influence of new factors. Thus, this work aims to identify the key parameters of the political process in the Middle East region.